The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/modpathol.2010.153
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor in adrenocortical tumors: analysis of gene sequence, protein expression and correlation with clinical outcome

Abstract: Adrenocortical carcinoma is a rare but highly malignant neoplasm with still limited treatment options. Epidermal growth factor receptor (EGFR) has been shown to be overexpressed in many solid tumors, but its expression in adrenocortical carcinoma has been studied only in a limited number of cases. Therefore, we analyzed the expression of EGFR in 169 adrenocortical carcinoma samples and compared it with 31 adrenocortical adenomas. Additionally, in 30 cases of adrenocortical carcinoma, exons 18-21 of the EGFR ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 44 publications
2
38
0
2
Order By: Relevance
“…The observed mutations were also described earlier in lung and colon carcinoma, but the response to EGFR-TKI therapy was not reported (23,24,25). Recently, Adam et al (22) found no mutations in 30 ACCs.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The observed mutations were also described earlier in lung and colon carcinoma, but the response to EGFR-TKI therapy was not reported (23,24,25). Recently, Adam et al (22) found no mutations in 30 ACCs.…”
Section: Discussionsupporting
confidence: 51%
“…Until now, only four mutations of the EGFR TK domain have been reported in ACC (21,22). Kotoula et al described four activating EGFR mutations, three missense (c.2168TOC, exon 18, c.2354COA, exon 20, and c.2533GOA, exon 21) and one non-sense mutation (c.2193GOA, exon 19) in 35 ACCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from transcriptome analyses, one of the most common methods to screen a large number of samples is tissue microarray: it has been widely used for immunohistochemistry studies on adrenocortical tumours [21,34,51,52,67,69,80,168].…”
Section: Molecular Research Methodsmentioning
confidence: 99%
“…Likewise, epidermal growth factor receptor (EGFR) shows elevated levels in adrenocortical carcinomas [78][79][80][81]. EGFR is a potential malignancy marker, as its expression is significantly higher in carcinomas than in adenomas.…”
Section: Other Growth Factors and Their Receptorsmentioning
confidence: 99%